Efficient Syntheses of Quinolizidine-Type Poison-Frog Alkaloids via Michael-Type Conjugate Addition. (April 2018) - Zhou, De-Jun; Zhai, Yang-Yang; Kong, Ji-Chuan; Wang, Zhen-Hui; Gong, Xue-Yun; Huang, Mei; Yin, Shu-Qiang
Efficient and flexible syntheses of 1, 4-disubstituted quinolizidine-type poison-frog alkaloids using the highly stereoselective Michael-type conjugate addition reaction as the key step are described. The 1, 4-disubstituted quinolizidine poison-frog alkaloids 233A, 235U and 251AA are reported.